DE NOMES E TÚMULOS:uma leitura de Jude Stéfan - Campos, Gabriela M. Nobre S. (2010)
This study aims to investigate the poetics of Jude Stefan, contemporary French poet, especially his relationship with the tradition of Letters. Placing an entire chorus of voices to speak from the dead, Stefan makes this relationship to tradition related to death and its figurations. Death, a central theme of this poetic, unfolds from theme to image, from image to figuration forming this way intricate paradoxes that we do not aim to solve, but somehow elucidate, thinking this poetry in the light of the concept of Neo-Baroque.